Interest Rate, Service Quality And Customer Satisfaction In Majesty Golden Raya Rural Credit Bank Company - Simanjuntak, Jontro; Jenni, (Online Journal for TVET Practitioners, 2020)
This research aims to analyze effects of interest rate on customer satisfaction, effects of service quality on customer satisfaction and effects of interest rate and service quality on customer satisfaction in Majesty Golden Raya Rural Credit Bank. This research used causality descriptive research design by using primary data as its source of data. These research respondents are customers in Majesty Golden Raya Rural Credit Bank. There are 128 active customers in credit transaction as the research samples. Data collection technique used questionnaire. Data analysis used descriptive analysis method to describe the research variables. This research also tested data quality, regression equation test and research hypotheses testing. Results prove that interest rate affects significantly on customer satisfaction. Service quality affects significantly on customer satisfaction. Interest rate and service quality affect significantly on customer satisfaction. This research conclusion is that interest rate and service quality affect on banking customer satisfaction and to improve customer satisfaction, it is necessary to improve employee product knowledge and soft skills.